Statistical Investigation of Wave Propagation in the Quiet-Sun Using IRIS Spectroscopic Observations - Sangal K.; Srivastava A.K.; Kayshap P.; Yuan D.; Scullion E. (My University, 2025)
In this analysis, we use spectroscopic observations of the quiet Sun made by the IRIS instrument and investigate wave propagation. We analyze various spectral lines formed in different atmospheric layers, such as the photosphere, chromosphere, and transition region. We examine the Doppler velocity time series at various locations in the quiet Sun to determine the dominant oscillation periods. Our results executing statistical analysis resemble those of the classical physical scenario, indicating that the photosphere is mainly characterized by the dominant 5 minute period, while the chromosphere is primarily associated with the 3 minute oscillation period. In the transition region, we observe a variety of oscillation periods, with dominant periods of 3, 8, and 12 minutes. We estimate the cutoff frequency by deducing the phase difference between two Doppler velocity time series obtained from spectral line pairs in different atmospheric layers formed at different temperatures. This reveals a significant correlation between 3 minute periods in the transition region and photospheric oscillations, suggesting that these oscillations in the transition region might propagate from the photosphere. Additionally, we analyze the phase difference between chromospheric oscillations and photospheric oscillations, demonstrating that only the 3 minute oscillations propagate upward. Based on the statistical analyses, we suggest the presence of magnetoacoustic waves in the solar atmosphere, some of which are propagating from the lower solar atmosphere upward, while some others are propagating downward. The transition region carries both long-period oscillations generated in situ and some photospheric oscillations that are also able to reach there from below. © 2024. The Author(s). Published by the American Astronomical Society.